2014
DOI: 10.1039/c4ee00612g
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical electrospun nanofibers for energy harvesting, production and environmental remediation

Abstract: As the demand for energy is rapidly growing worldwide ahead of energy supply, there is an impulse need to develop alternative energy-harvesting technologies to sustain economic growth. Due to their unique optical and electrical properties, one-dimensional (1D) electrospun nanostructured materials are attractive for the construction of active energy harvesting devices such as photovoltaics, photocatalysts, hydrogen energy generators, and fuel cells. 1D nanostructures produced from electrospinning possess high c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
152
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(152 citation statements)
references
References 297 publications
(279 reference statements)
0
152
0
Order By: Relevance
“…The AQY decreases with increasing wavelength, and the longest wavelength is suited to overall water splitting, in accordance with the DRS spectra of photocatalyst 3 [17]. It is noted that the photocatalytic reaction proceeds through light absorption [63].…”
Section: Photocatalytic Activitymentioning
confidence: 62%
See 1 more Smart Citation
“…The AQY decreases with increasing wavelength, and the longest wavelength is suited to overall water splitting, in accordance with the DRS spectra of photocatalyst 3 [17]. It is noted that the photocatalytic reaction proceeds through light absorption [63].…”
Section: Photocatalytic Activitymentioning
confidence: 62%
“…Afterwards, the H 2 generation rate reversely reduced with the amount of Ag NPs up to 15 wt%. This can be owing to more hole-electron recombination in the composite 4 and 5 [63].…”
Section: Photocatalytic Activitymentioning
confidence: 97%
“…Electrospinning is an effective and simple method for preparing nanofibers with 1D nanostructure [27][28][29][30]. This method is applied in many areas such as filtration, optical and chemical sensors, biological scaffolds, electrode materials, drug delivery materials, photocatalysts, and nanocables [31][32][33][34][35][36][37]. Accordingly, here we employed electrospinning method to prepare magnetic and color- 3 phen)]/PVP nanofiber).…”
Section: Introductionmentioning
confidence: 97%
“…and Kumar et al 39 reported that electrospun nanobers of LiMn 2 O 4 had outstanding properties for lithium batteries. Recently, Zhou and co-workers 41 prepared an ultra-long spinel lithium manganese oxide nanober cathode via an electrospinning method, and the cathode materials showed a porous "network-like" morphology with nanosize diameters ($170 nm), microsize lengths, ($20 mm) and a pure spinel structure.…”
mentioning
confidence: 99%
“…Hierarchical porosity and structures are involved in newly developed materials for energy storage, which include the advantages of nanoparticles and eliminate their drawbacks to some degree. 57 Hierarchical LiMn 2 O 4 microspheres, 58-60 nanobers, 39 and doughnut-shaped 61 structures are common. A hierarchical LiMn 2 O 4 phase with a layered nanostructure was also studied by Lee et al, and it exhibited a high discharge capacity and excellent cycling stability at elevated temperature (60 C).…”
mentioning
confidence: 99%